Maximizing Power Efficiency with Asymmetric Multicore Systems. - FEDOROVA, ALEXANDRA; SAEZ, JUAN CARLOS; SHELEPOV, DANIEL; PRIETO, MANUEL (Communications of the ACM, 2009)
The article discusses the development of software that takes advantage of the design of asymmetric multicore processors (AMPs). The potential for AMPs to conserve large amounts of electricity due to their design, which consists of cores using the same instruction set architecture (ISA) but with differing performance and power characteristics, is discussed. The inclusion of several powerful, high-power-consumption cores along with a large number of slower, low-power-consumption cores in the design of an AMP is mentioned, noting that processor-intensive, single-threaded, sequential tasks are best served by the more powerful cores while parallel applications run most efficiently on the large number of simpler cores.